Atención al cliente y su influencia en el nivel de ventas de la Ferretería Solano E.I.R.L. en el primer semestre del 2016 del distrito de Trujillo - Zelada Vergaray, Luisa Guadalita (2016)
The present work of investigation it was elaborated by the purpose of determining the attention to the client and influence at the level of sales in the HARDWARE STORE SOLANO EIRL In the first semester of 2016 of District of Trujillo. The problem was: the problems were: does the attention to the client in the level of sales of HARDWARE STORE SOLANO EIRL In the first semester of 2016 of District of Trujillo? The hypothesis is the attention to the client influences in a significant way the level of sales of HARDWARE STORE SOLANO EIRL In the first semester of 2016 of District of Trujillo. The research design it is of transactional type, Grounds, of cross section using a representative sample of 333 clients who evaluated the quality of attention to the client offered by the personnel of the HARDWARE STORE SOLANO EIRL So it was work a sample population 10 worker to determine the factors that influence the customer support. The used instrument was the questionnaire applied to both samples. Between the results mas relevant It is found that the attention to the client in the area of despatch Between regular and bad and the factor that influences in the result It is the lack of training focused on the client By means of the investigation one proposes a protocol of attention to the client who will allow the company to increase his sales and the loyalty of his clients.